Male Breast Cancer- Report of Two Cases - Uddin, M Dayem; Hannan, ABM Abdul (TAJ: Journal of Teachers Association, 2009)
Male breast cancer is rare. It accounts for 0.2% of all cancers, and 1% all breast cancers. Most patients present late for several reasons, including the absence of early signs and symptoms, and reduced awareness of the existence of such pathology among patients and physicians, Reporting these cases from among the Bangladeshi population, we tried to observe any differences in clinical manifestation from those reported in the literature, and aimed to increase the value assigned to male breast as a source of pathology among patients and physicians as well. doi: 10.3329/taj.v21i1.3226 TAJ 2008; 21(1): 80-82